KOMPETENSI KEPALA SEKOLAH DALAM PELAKSANAAN MPBS DI SMK PEMUDA BLITAR - Soebiantoro Soebiantoro (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2014)
This article is a research report on the implementation of School Based Management (SBM) by a principal of SMK Pemuda Blitar. As an action research, this study observed the implementation of SBM inductively.  The study revealed that evidences that support effectiveness of ruling staff and administration is strongly identified.  Participations and self-reliance decision making proceess, individual invlolvement and group dynamics are productively desmonstrated.